Atheism in US and UK Newspapers: Negativity about Non-Belief and Non-Believers - A. Maurits van der Veen; Erik Bleich (Religions, 2021)
Atheists are among the most disliked “religious” groups in the United States, but the origins of this aversion remain poorly understood. Because the media are an important source of public attitudes, we analyze coverage of atheism and atheists in American and British newspapers. Using computational text analysis techniques, including sentiment analysis and topic modeling, we show that atheism is portrayed negatively by the print media. Significantly, we show that greater negativity is associated with atheism as a concept than with atheists as individuals. Building on this insight, and challenging arguments that prominent atheist intellectuals attract negative coverage, we also find that coverage of famous atheists is actually more positive than that of atheists or atheism in general. Overall, our findings add a new dimension to scholarship on differences between individual-targeted and group-targeted tolerance in public attitudes, establishing for the first time that media coverage mirrors such differences.